Low rates of myocardial fibrosis and ventricular arrhythmias in recreational athletes after SARS-CoV-2 infection - Miljoen, Hielko; Favere, Kasper; Van De Heyning, Caroline; Corteville, Ben; Dausin, Christophe; Herbots, Lieven; Teulingkx, Tom; Bekhuis, Youri; Lyssens, Malou; Bogaert, Jan; Heidbuchel, Hein; Claessen, Guido (Frontiers in Cardiovascular Medicine, 2024)
Introduction High rates of cardiac involvement were reported in the beginning of the coronavirus disease 2019 (COVID-19) pandemic. This led to anxiety in the athletic population. The current study was set up to assess the prevalence of myocardial fibrosis and ventricular arrhythmias in recreational athletes with the recent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Methods Consecutive adult recreational athletes (≥18 years old, ≥4 h of mixed type or endurance sports/week) underwent systematic cardiac evaluation after a prior confirmed COVID-19 infection. Evaluation included clinical history, electrocardiogram (ECG), 5-day Holter monitoring, and cardiac magnetic resonance (CMR) imaging with simultaneous measurement of high-sensitive cardiac Troponin I. Data from asymptomatic or mildly symptomatic athletes (Group 1) were compared with those with moderate to severe symptoms (Groups 2–3). Furthermore, a comparison with a historical control group of athletes without COVID-19 (Master@Heart) was made. Results In total, 35 athletes (18 Group 1, 10 female, 36.9 ± 2.2 years, mean 143 ± 20 days following diagnosis) were evaluated. The baseline characteristics for the Group 1 and Groups 2–3 athletes were similar. None of the athletes showed overt myocarditis on CMR based on the updated Lake Louise criteria for diagnosis of myocarditis. The prevalence of non-ischemic late gadolinium enhancement [1 (6%) Group 1 vs. 2 (12%) Groups 2–3; p = 0.603] or ventricular arrhythmias [1 Group 1 athlete showed non-sustained ventricular tachycardia (vs. 0 in Groups 2–3: p = 1.000)] were not statistically different between the groups. When the male athletes were compared with the Master@Heart athletes, again no differences regarding these criteria were found. Conclusion In our series of recreational athletes with prior confirmed COVID-19, we found no evidence of ongoing myocarditis, and no more detection of fibrosis or ventricular arrhythmias than in a comparable athletic pre-COVID cohort. This points to a much lower cardiac involvement of COVID-19 in athletes than originally suggested.